Comparison of the Efficacy of Local Infiltration and Mandibular Block Anesthesia With Articaine for Harvesting Ramus Grafts - GÖÇMEN, GÖKHAN; ÖZKAN, YAŞAR (W B SAUNDERS CO-ELSEVIER INC, 2016)
Purpose: We compared the efficacy of local infiltrative anesthesia and regional mandibular block anesthesia using articaine to harvest ramus grafts and the postoperative sequelae. Materials and Methods: A total of 20 patients with alveolar bone deficiency participated in the present comparative, prospective, randomized study. The first group received regional anesthesia with the mandibular block technique (group A; n = 10), and those in the second group received local infiltration anesthesia (group B; n = 10). Intraoperative pain and bleeding were evaluated as the primary outcome variables. The visual analog scale (VAS) scores were compared at 0.5, 1, 2, and 4 hours postoperatively. The maximal interincisal mouth opening (MIO) (on days 3 and 7) and VAS scores (at 6, 12, 24, and 48 hours and on days 3 and 7) were compared as secondary outcome variables. The correlation between pain (VAS scores) and trismus (MIO) were also compared. Results: A painless procedure was performed in both groups. The VAS score, MIO, and intraoperative bleeding were not significantly different between the 2 groups. Paresthesia was not observed in either group postoperatively. No statistically significant correlations were found between the VAS scores and MIO. Conclusions: Local infiltrative anesthesia preserves almost the same depth of anesthesia as mandibular block anesthesia. No differences were found between these techniques in terms of efficacy and postoperative sequelae during and after ramus graft harvest. Thus, using articaine with a local infiltration technique is an alternative to mandibular block anesthesia during ramus graft harvesting and results in a reduced risk of inferior alveolar nerve damage. (C) 2016 American Association of Oral and Maxillofacial Surgeons.
Keywords: 3RD MOLAR SURGERY; INFERIOR ALVEOLAR NERVE; 4-PERCENT ARTICAINE; IMPLANT PLACEMENT; DOUBLE-BLIND; REMOVAL; BONE; PAIN